Effect of Gamification on the Development of Digital Competencies of Regular Basic Education Teachers - Collantes Robles, Eliana Vanessa (2024)
In the digital age, teachers’ digital competencies are important for effective education, yet many educators, particularly in Latin America, lack these essential skills. While gamification has shown promise in various education contexts, its effectiveness for developing teachers’ digital competencies remains understudied, especially in the Latin American setting. This study aimed to examine the effect of gamification on the development of digital competencies of basic education teachers in Trujillo, Peru. A quasi-experimental design was used, and 60 primary-level teachers were selected through convenience sampling; they were randomly assigned to either an experimental (n = 30) or control (n = 30) group. The experimental group participated in a two-month program consisting of 15 gamified sessions, whereas the control group received no intervention. Data were collected via an adapted version of the Teacher Digital Competence Questionnaire in pretest and posttest phases. Descriptive statistics, Mann-Whitney U tests, and Kruskal-Wallis tests were employed for data analysis. The results reveal significant improvements in the experimental group’s digital competencies across all dimensions (information literacy, communication, content creation, safety, and problem-solving), with 93.3% achieving the “achieved” level postintervention, compared with 30% of the control group. Inferential analysis confirms significant differences between groups in the posttest phase (Mann-Whitney U = 96.5, p < .05). These findings suggest that gamification is an effective strategy for developing teachers’ digital competencies, and can contribute valuable empirical evidence to the field of education technology and holds important implications for teacher training and education policies in Latin America.